A novel method for testing and determining ILSS for marine and offshore composites. (15th July 2019) - Gagani, Abedin I.; Krauklis, Andrey E.; Sæter, Erik; Vedvik, Nils Petter; Echtermeyer, Andreas T.
Abstract: A novel method is proposed for interlaminar shear testing of marine composites, which accelerates fluid saturation: the I-beam short beam shear test. A layered finite element (FE) model is employed to explain the nonlinear behavior of the short beam shear experiment. Using this model, rectangular and I-beam short beam shear results are compared, yielding consistent results. Dry and saturated specimens are also compared for the I-beam geometry proposed. The model can simulate these effects and enables attributing the nonlinear behavior of the composite interlaminar shear response to the plasticity of the resin rich inter-ply. In both dry and saturated conditions, the interlaminar shear strength of the composite can be estimated mainly from the matrix properties.